2014
DOI: 10.1160/th13-09-0793
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of first and recurrent venous thromboembolism: A population-based cohort study in patients without active cancer

Abstract: Contemporary data from population studies on the incidence and complications of venous thromboembolism (VTE) are limited. An observational cohort study was undertaken to estimate the incidence of first and recurrent VTE. The cohort was identified from all patients in the UK Clinical Practice Research Datalink (CPRD) with additional linked information on hospitalisation and cause of death. Between 2001 and 2011, patients with first VTE were identified and the subset without active cancer-related VTE observed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
223
3
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 252 publications
(253 citation statements)
references
References 18 publications
12
223
3
15
Order By: Relevance
“…The strengths of this study include the use of a validated venous thromboembolism algorithm, a non-venous thromboembolism cohort matched on known and suspected confounding factors that are or may be causes of prescriptions for testosterone or of venous thromboembolism, and the availability of full prescription data allowing investigation of risk of venous thromboembolism by time since starting or stopping testosterone treatment 22. In addition, we were able to adjust for other potential confounders known to be associated with the risk of future venous thromboembolism and to reduce confounding by indication by matching on history of hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strengths of this study include the use of a validated venous thromboembolism algorithm, a non-venous thromboembolism cohort matched on known and suspected confounding factors that are or may be causes of prescriptions for testosterone or of venous thromboembolism, and the availability of full prescription data allowing investigation of risk of venous thromboembolism by time since starting or stopping testosterone treatment 22. In addition, we were able to adjust for other potential confounders known to be associated with the risk of future venous thromboembolism and to reduce confounding by indication by matching on history of hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
“…We applied a validated algorithm for venous thromboembolism to identify the first occurrence 22. Venous thromboembolism comprised pulmonary embolism and deep vein thrombosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [15,22] reported an equal prevalence of spontaneous and non-spontaneous VTE. However, we observed a high prevalence of spontaneous VTE (68.3%) versus non-spontaneous (31.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Any type of thrombosis was included except those related to cancer. VTE was classified as either unprovoked or spontaneous or provoked or nonspontaneous (one or more provoking factors within 3 months previous to an event) [15,16]. In this last group, provoking factors were: surgery, immobilization, pregnancy, oral contraceptive, prothrombotic nonneoplastic diseases and others.…”
Section: Samplementioning
confidence: 99%